2013
DOI: 10.1109/tase.2012.2230627
|View full text |Cite
|
Sign up to set email alerts
|

Similarity Analysis of Industrial Alarm Flood Data

Abstract: Flooding of alarms is a very crucial problem in process industries. An alarm flood makes an operator ineffective of taking necessary actions, and often risking an emergency shutdown or a major upset. In this work, the flooding of alarms is discussed based on the standards presented in ISA 18.2. A new analysis method is proposed to investigate similar alarm floods from the historic alarm data and group them on the basis of the patterns of alarm occurrences. A case study on real industrial alarm data is also pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(53 citation statements)
references
References 7 publications
0
53
0
Order By: Relevance
“…Our study shows that the flood distance measure in [1] behaves significantly different from the other analysed distance measures; in particular, the other measures produce a more stable clustering in the presence of noise in the data.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…Our study shows that the flood distance measure in [1] behaves significantly different from the other analysed distance measures; in particular, the other measures produce a more stable clustering in the presence of noise in the data.…”
Section: Introductionmentioning
confidence: 57%
“…Analysis of the behaviour of the distance measure can then help choose the most suitable distance measure. We also reproduce and extend the alarm flood detection and clustering approach by Ahmed et al [1] with additional similarity measures based on Term frequency-inverse document frequency (TF-IDF) representation [12] and Levenshtein distance [14], apply these measures to a large real industrial alarm log and evaluate them using our validation method.…”
Section: Introductionmentioning
confidence: 99%
“…In the research of [3], an evaluation of the alarm filters which are suggested in [1] to find the optimal ones. In the research of [1] clustering of alarm is done by evaluating the consecutive occurrence pattern of alarms.…”
Section: Related Workmentioning
confidence: 99%
“…In the research of [1] clustering of alarm is done by evaluating the consecutive occurrence pattern of alarms. Also, various alarm management techniques including frameworks, data filtering, alarm delay and alarm deadlines are suggested, in order to design an optimal alarm system [5].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation